STUDI KOMPUTASI SEMIBUCKMINSTERFULLERENE SEBAGAI PENYIMPAN HIDROGEN MENGGUNAKAN METODE PERHITUNGAN DENSITY FUNCTIONAL THEORY. - Digva Willyan; Rahmat Gunawan; Veliyana Londong Allo (JURNAL KIMIA MULAWARMAN, 2020)
Hydrogen is an alternative energy source for fossil fuels. One of molecules that have an ability to store hydrogen is Semibuckminsterfullerene. This study was conducted to find out the optimum distance in adding hydrogen and the phenomenon of energy produced when adding hydrogen from 10 molecules to 100 molecules. Semibuckminsterfullerene was calculated using Density Functional Theory method, B3LYP with a basis set of 6-31G*. The optimum distance of Semibuckminsterfullerene with hydrogen was 3 ? Furthermore, the results of adding hydrogen from 10 to 100 molecules showed a decrease in energy due to the bowl-shaped structure of Semibuckminsterfullerene